2017
DOI: 10.1186/s40880-016-0175-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA mismatch repair gene polymorphisms and platinum-based chemotherapy toxicity in non-small cell lung cancer patients

Abstract: BackgroundChemotherapy toxicity is a serious problem from which non-small cell lung cancer (NSCLC) patients suffer. The mismatch repair (MMR) system is associated with platinum-based chemotherapy toxicity in NSCLC patients. In this study, we aimed to investigate the relationship between genetic polymorphisms in the MMR pathway and platinum-based chemotherapy toxicity in NSCLC patients.MethodsA total of 220 Chinese lung cancer patients who received at least two cycles of platinum-based chemotherapy were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Therefore, several studies have focused on the assessment of the MMR status, as this may have a significant predictive value for these patients. [23,24,34,36,37].A number of regulatory molecules such as miRNAs have been suggested to be implicated in the regulation of MMR genes [38][39][40][41][42][43][44][45][46]. In particular, recent studies support a cross-talk between specific miRNAs and MMR genes [41][42][43].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several studies have focused on the assessment of the MMR status, as this may have a significant predictive value for these patients. [23,24,34,36,37].A number of regulatory molecules such as miRNAs have been suggested to be implicated in the regulation of MMR genes [38][39][40][41][42][43][44][45][46]. In particular, recent studies support a cross-talk between specific miRNAs and MMR genes [41][42][43].…”
mentioning
confidence: 99%
“…Therefore, several studies have focused on the assessment of the MMR status, as this may have a significant predictive value for these patients. [23,24,34,36,37].…”
mentioning
confidence: 99%
“…Therefore, MutSα and MutLα are important proteins in the MMR system and are used to cooperate the mismatch detection and repair events. In previous study, we found that MutSα and MutLα genes were associated with the toxicity of platinum-based chemotherapeutic in lung cancer [30,31].…”
Section: Ivyspringmentioning
confidence: 93%
“…Finally, Thirty-five SNPs were genotyped in the patients (Table 1). In our previous studies, the SNPs were investigated to be associated with platinum-based chemotherapy toxicity [30].…”
Section: Snp Selection Dna Extraction and Genotypingmentioning
confidence: 99%
“…Many studies suggested that MMR genes played important roles in chemotherapy. [49][50][51][52] Is this mutation important for the prediction of chemotherapy? Considering that the proband's chemotherapy regimen is oxaliplatin and 5-fu, and irinotecan is a commonly used chemotherapy drug for colorectal cancer, we use these three drugs for cell viability experiments.…”
Section: The Frameshift Mutation Was Found In All Cancer Diagnosed Mementioning
confidence: 99%